Analysis of clinical efficacy and safety of intravenous use of diclofenac for the prevention of postoperative pain: current status and strategic aspect - Litvinova, Elena (ScienceRise: Pharmaceutical Science, 2020)
The aim of the work is to analyze and systematize the literature data regarding the current state and strategic aspect of intravenous use of diclofenac for the prevention of postoperative pain, namely clinical efficacy and safety. Materials and methods. Studies were conducted using databases on the Internet: PubMed; Food and Drug Administration, European Medicines Agency. It has used retrospective, logical, research methods, content analysis. Results. Conducted clinical data analysis indicates that diclofenac sodium, when administered intravenously, has an opioid-saving effect, is effective in patients experiencing acute postoperative pain, or as part of a multimodal analgesic strategy to achieve perioperative pain control. This increases the possibility of relief of pain and promotes accelerated rehabilitation after surgery, reduces the need for opiates. The incidence of side effects with intravenous diclofenac was similar to that seen with other treatments. New opportunities of the strategic aspect of intravenous use of diclofenac is related to the use of Dyloject, Hospira Inc., USA, which has improved solubility, shorter administration time than infusion. The incidence of thrombophlebitis on treatment with Dyloject was less pronounced compared to Voltarol. Conclusions. Thus, the experience of clinical intravenous use of diclofenac sodium for the prevention of postoperative pain has confirmed its efficacy, favorable safety profile and the ability to reduce the need for opiates. The promising strategic aspect is the creation of domestic diclofenac sodium preparations for intravenous administration, which have improved solubility, shorter administration time than infusions and have no additional safety risk